Analysing the trade of meat products between Namibia and SADC countries - Andreas, Erastus (Namibia University of Science and Technology, 2023)
The study examines the trade in meat products between Namibia and SADC countries. Cross-section data from the UN COMTRADE, Namibia Statistic Agency (NSA), and CEPII for 2000-2020 was used. To achieve the aim of the study, estimation from the gravity model, Stochastic Frontier Analysis (SFA), specifically using Error Components Frontier with a fixed effects model (assumes country specific and time-invariant inefficiencies), The Trade Intensity index (TII) was adopted to estimate the products that have a major effect on Namibia’s meat trade with SADC countries. Technical Efficiency Effects Frontier (fixed effects model) was used to estimate Namibia's potential trade with other SADC countries. The study established a strong positive relationship between real GDP and trade. A positive coefficient was found between the population and trade. However, distance had a negative correlation coefficient. The estimates for the real GDP coefficient are statistically significant, with a level of at least 5%. The positive and significant coefficient of real GDP implied that Namibia's trade value increased with the partner countries. The distance estimate was negative, as predicted by gravity theory. According to this finding, the greater the distance between Namibia and its trading partners, the less likely they are to trade. This variable is a proxy for transportation and other trade costs, such as communication and transaction costs. Because of this, the price increases with distance. In other words, trade volume between Namibia and its SADC members decreases proportionately as distance increases. Namibia's trade intensity trend in meat products has been on the rise from 2000 until 2020. In addition, the study shows that Namibia has performed relatively poorly and has a significant trade potential. The mean trade efficiency in meat products between Namibia and SADC countries is estimated to be approximately 22%. Mean technical efficiency shows interesting results as some SADC countries with a low percentage of trade efficiency tend to have strong potential for export growth for Namibia’s exports of meat products. Furthermore, Trade efficiency is more than 50% for DRC, Zimbabwe, and Botswana; however, it is less than 50% for most SADC countries. Based on the distance and size of economies, SADC offers export market opportunities for Namibia’s meat products. To understand the determinants of trade and relationships, it is crucial that the study advises conducting additional research to assess the competitiveness of Namibia’s meat products in the markets in the SADC region, identify and attempt to resolve trade impediments in the SADC region, evaluate the complete liberalization of trade in the agricultural sector and other sectors that contribute to the GDP of the country.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Agribusiness Management at the Namibia University of Science and Technology.
Keywords: Trade flow; SADC; Meat products; Gravity model; Stochastic Frontier; Trade intensity